The Effectiveness of Health Management for Pre-Diabetes in Khon Kaen Province - Jaklang, Thanut (Journal for Developing the Social and Community, 2017)
Diabetes is the major health problem of the world, which tends to increase steadily. The objectives of this study were to study the effectiveness of health management for pre-diabetes people and the current situation of management factors, social support factors, potential factors, and health management factors among pre-diabetes people in Khon Kaen Province. The subjects were 613 pre-diabetics people by using Multi-stage sampling. The tool used for the questionnaire was the discriminative power of 0.20-0.78 and the total reliability was 0.98. The statistics used for data analysis were frequency, percentage, mean, standard deviation and rate. The results were as follows: The effectiveness of health management for pre-diabetes people in Khon Kaen Province; the rate of decline in blood sugar level (BSL), body mass index (BMI) and waist circumference (WC) in the period of 3 years, 2015 to 2017 was low. The current situation of the management factors of district health offices; health policy promotion for the sample was at a high level, the effectiveness of health promotion policy promotion was at a moderate level, encourage participation in health promotion and health promotion controlling were at the high level. Social support factors; family involvement, cooperation of public health personnel and community participation were at the high level. Potential factor; most of them had moderate knowledge about diabetes, health beliefs was at the high level, Intent to change health behavior and the emotional and stress levels were at moderate level and Health management factors; food control, exercise and emotional and stress management control were at moderate level.